Gender Nonconformity and Peer Victimization: Sex and Sexual Attraction Differences by Age. Issue 2 (12th February 2020) - van Beusekom, Gabriël; Collier, Kate L.; Bos, Henny M. W.; Sandfort, Theo G. M.; Overbeek, Geertjan
Abstract : Among 2, 185 Dutch adolescents (ages 11 to 18), we assessed whether the association among gender nonconformity, homophobic name-calling, and other general peer victimization differs for boys and girls and for youth with and without same-sex attraction (SSA). We also examined whether sex and sexual attraction differences in the association between gender nonconformity and both types of peer victimization are dependent upon adolescents' age. Data were collected in the academic year 2011–2012. Results showed that gender nonconformity was positively associated with homophobic name-calling and general peer victimization. These associations were stronger for boys compared with girls and were also stronger with increasing levels of SSA. Sex differences in the relationship between gender nonconformity and general peer victimization were significant for early and middle adolescents but not for late adolescents. Sexual attraction differences in the relationship between gender nonconformity and both types of peer victimization were significant for early and middle adolescents but not for late adolescents. These results emphasize that key educational messages that address sexual and gender diversity should be delivered during childhood before early adolescence.